Duties of The Church Diaconal According to Acts 6:1-7 - Imel Poceratu (East Asian Journal of Multidisciplinary Research, 2023)
Diaconal ministry to those in need is a statement that needs to be proven by conducting a study based on the original manuscripts of the Bible. So to achieve this goal, the author conducts literary research using biblical studies of the New Testament and using a historical-critical approach. As the number of disciples grew, there was one ministry that the apostles neglected, the "table ministry." This ministry is concerned with providing daily assistance to widows and the poor. Democratically, the apostles proposed that the disciples choose seven well-known, Spirit-filled, and wise men to carry out this ministry. Many people consider the ministry of the Diakonia separate from the ministry of the Word. But there is an interesting thing that the author finds here, namely diaconal ministry is one form of word ministry.